1964
DOI: 10.1063/1.1725879
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Molecular Aggregates. I. Classical Model of Electronic Absorption and Refraction

Abstract: A theoretical classical model is developed to predict the absorption and refraction of an aggregate of monomer units (a molecular aggregate, molecular crystal, or polymer) at any frequency. The monomers are treated as having complex electronic polarizabilities whose frequency dependence is determined by the absorption bands of the isolated monomers. Polarizations in the aggregate induced by incident light are modified by Coulombic interactions between the monomers. No first-order approximation is involved as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(143 citation statements)
references
References 15 publications
5
134
0
1
Order By: Relevance
“…37 This result clearly indicates that the Ag-NPs in our study retained their shape as spherical particles in 2-propanol with the aid of the PVP stabilizer an increased temperature. Figure 2 shows the UV-Vis absorption spectra of the AgNPs colloidal solution stabilized with PVP taken at different reaction times between 3 min and 10 min at 65 o C. The UVVis absorption peaks also appeared at 360 nm with a shoulder at 410 nm at the initial time.…”
supporting
confidence: 59%
“…37 This result clearly indicates that the Ag-NPs in our study retained their shape as spherical particles in 2-propanol with the aid of the PVP stabilizer an increased temperature. Figure 2 shows the UV-Vis absorption spectra of the AgNPs colloidal solution stabilized with PVP taken at different reaction times between 3 min and 10 min at 65 o C. The UVVis absorption peaks also appeared at 360 nm with a shoulder at 410 nm at the initial time.…”
supporting
confidence: 59%
“…The method was firstly developed by [13,14] and [38]. The main idea is to discretize the nanoparticle into a set of N elements or dipoles with polarizabilities α j , located at r j .…”
Section: The Discrete Dipole Approximation Methodsmentioning
confidence: 99%
“…30 For the case of more complex NPs, in 1964 Howard DeVoe introduced the discrete dipole approximation (DDA) method. 31 On the other hand, the first documented studies about ESPs date from 1902, when Robert Woods observed anomalies in optical reflection measurements on metallic gratings. 32 Later, the anomalies observed by Woods were studied by Ugo Fano and these were associated with electromagnetic waves on the surface of the metallic gratings.…”
Section: Brief Historymentioning
confidence: 99%